The effects of genetic polymorphisms on benzene-exposed workers: A systematic review (2021)
ABSTRACT: Background and Aims: Benzene is a group I carcinogen, which has been associated with leukemia and myelodysplastic syndrome. Moreover, it has been proposed that polymorphisms in benzene metabolizing genes influence the outcomes of benzene exposure in the human body. This systematic review aims to elucidate the existent relationship between genetic polymorphisms and the risk of developing adverse health effects in benzene-exposed workers. Methods: Three databases were systematically searched until April 2020. The preferred reporting items for systematic reviews and meta-analyses method was used to select articles published between 2005 and 2020. Quality assessment and risk of bias were evaluated by the Newcastle-Ottawa scale. Results: After full-text evaluation, 36 articles remained out of 645 initially screened. The most studied health effects within the reviewed papers were chronic benzene poisoning, hematotoxicity, altered urinary biomarkers of exposure, micronucleus/ chromosomal aberrations, and gene methylation. Furthermore, some polymorphisms on NQO1, GSTT1, GSTM1, MPO, and CYP2E1, among other genes, showed a statistically significant relationship with an increased risk of developing at least one of these effects on benzene-exposed workers. However, there was no consensus among the reviewed papers on which specific polymorphisms were the ones associated with the adverse health-related outcomes, except for the NQO1 rs1800566 and the GSTT1 null genotypes. Additionally, the smoking habit was identified as a confounder, demonstrating worse health outcomes in exposed workers that smoked. Conclusion: Though there is a positive relationship between genetic polymorphisms and detrimental health outcomes for benzene-exposed workers, broader benzeneexposed cohorts that take into account the genetic diversity of the population are needed in order to determine which specific polymorphisms incur in health risks.